Gambaran Kecerdasan Emosional Dengan Gaya Manajemen Konflik Perawat - Putri Dwi Helga; Stevani J. Sinuhaji; Cristin E. Manurung; Rika Endah Nurhidayah; Pohan, Novi Hanjani (Universitas Nasional Karangturi, 2023)
Conflict is a complex process that cannot be avoided. Conflict needs to be managed positively so that it has a good impact on the development of individuals and organizations. Conflict management is very important in solving problems in the workplace, especially for nurses. Conflict management has a close relationship with the emotional intelligence of nurses in building and maintaining cooperation in order to produce the desired resolution. The purpose of this study was to determine the description of emotional intelligence with the conflict management style of nurses. The method used is a search for management style journals in nursing conflict with nurses' emotional intelligence, including designs, studies, samples, and research results of journals that are searched. The journals collected are the latest published journals and have been selected through Google Scholar, an international journal indexed by Sinta. The results of the study show that there is a relationship between emotional intelligence and nurses' conflict management. Conflict and its management are motivated by many factors, therefore it is important to properly assess the influencing factors that are expected to have an impact on the conflict management approach used by nurses. So that nurses with high emotional intelligence are able to resolve conflicts and choose a good conflict management style. Keywords : Inteligent emotional, style management, nurse’s conflict management